Rockglaciers: Indicators for the Present and Former Geoecology in High Mountain Environments - Barsch, Dietrich (Springer, 1996)
Rockglaciers are the visible expression of the creep of mountain permafrost. They are indicative of special geo-ecologic and geomorphic conditions regarding thermal situation, talus production, hydrology, and hazards in high mountain environments of all major mountain systems on earth. As relict features, they are of great paleoclimatic value. This book presents a systematic treatment of this landform in its environmental context
Keywords: Blockgletscher; Geoökologie; Glazialmorphologie; Hochgebirge